2016
DOI: 10.1001/jamaoto.2015.2849
|View full text |Cite
|
Sign up to set email alerts
|

Primidone Therapy for Essential Vocal Tremor

Abstract: Primidone therapy was an effective pharmacologic treatment for essential vocal tremor in 14 of 26 patients in this case series, providing an alternative to botulinum neurotoxin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A retrospective chart review (n=30) reported that approximately 50% (n=14) of patients taking primidone had improvement in vocal tremor. Head tremor does not consistently respond to primidone 127128129…”
Section: Treatment Of Essential Tremormentioning
confidence: 99%
“…A retrospective chart review (n=30) reported that approximately 50% (n=14) of patients taking primidone had improvement in vocal tremor. Head tremor does not consistently respond to primidone 127128129…”
Section: Treatment Of Essential Tremormentioning
confidence: 99%
“…Other agents include alternate beta-agonists and anticonvulsants as well as benzodiazepines and carbonic anhydrase inhibitors. It is important to note that although these medications usually do not completely resolve the tremor, they dampen its amplitude successfully in 25–55.6% of patients [ 49 , 50 , 51 ]. By comparison, BoNT has a reported 70% tremor reduction rate in the literature, and patient-reported vocal quality improvement in 56–100% of patients [ 45 , 46 , 47 , 48 , 85 ] (See Table 1 ).…”
Section: Vocal Tremormentioning
confidence: 99%
“…Whereas several pharmacologic options with level A or B evidence are available for the treatment of ET that affects the limbs, few such options are available for treating EVT. Efficacy studies for EVT primarily address BTA treatment, or have implemented open‐label designs or retrospective analyses to study pharmacological alternatives such as propranolol or primidone . Prospective studies that include strong experimental controls and objective measures of voice tremor are needed to determine the potential benefit of drug alternatives in EVT.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy studies for EVT primarily address BTA treatment, 14,40 or have implemented open-label designs or retrospective analyses to study pharmacological alternatives such as propranolol 26 or primidone. 41 Prospective studies that include strong experimental controls and objective measures of voice tremor are needed to determine the potential benefit of drug alternatives in EVT. Well-controlled, open-label, 18,42 and double-blind trials 17 of 1-octanol and OA have provided preliminary support for its ability to reduce magnitude of tremor in the limbs, but voice tremor was not addressed.…”
Section: Discussionmentioning
confidence: 99%